New positions of the Arbitrage Regulations of UNSITRAL: komparativiskiy approach - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
He article describes the changes of the Arbitration Regulations of UNSITRAL and makes it comparativeanalyze with the other international regulations.